Seroprevalence and geographical distribution of human T-lymphotropic virus type 1 among volunteer blood donors in endemic areas of Iran. Issue 1 (December 2017) - Karimi, Gharib; Zadsar, Maryam; Pourfathollah, Ali
Abstract Background Human T-cell lymphotrophic virus type 1 (HTLV-1) has a worldwide distribution and it is endemic in some regions of Iran. One of the most important routes of HTLV-1 transmission is via transfusion of contaminated blood components. The risk of transmission through asymptomatic blood donors, particularly in endemic areas should be considered and appropriately managed. The main objective of this study was to determine the seroprevalence and description the geographic distribution of HTLV-1 among voluntary blood donors in Iran. Methods This retrospective study carried out using the data obtained from the main database of the seven blood transfusion centers of Iranian Blood Transfusion Organization between 2009 and 2013. The presence of anti-HTLV-1/2 antibodies were primarily assessed using Enzyme-linked Immunosorbent Assay. The Ab Kit assay, contain antigens for the screening of antibodies to HTLV type 1 and 2. So, it is expressed as HTLV 1/2 assay. Samples that were positive by the western blot confirmatory test were considered as definite positive HTLV-1 or HTLV-2 cases. The main socio-demographic variables were; age, gender, donation history and marital status. Descriptive and analytical statistics were used to summarize the gathered data. The chi-Square Statistical test was used to test the association between groups, P-value of less than 0.05 was considered significant. Results A total of 1864489 blood donations were evaluated. There were 1840 confirmed HTLV-1 positive donations (0.098%). None were positive for anti-HTLV-2. The overall HTLV-1 prevalence was 98.7 per 100, 000 donations during the 5 year period. Seroprevalence was higher among females, married and older blood donors. The overall seropositivity among first time, regular and lapsed donors was, 0.29% (290/100000), 0.001% (1/100000) and 0.02% (20/100000) respectively. A significant difference was observed between regular and the first time (p <0.0001) and also between lapsed and regular blood donors (p <0.0001). Most of the HTLV-1 seropositive blood donors (175 per 100, 000) were from northeastern regions. We observed a gradual decline in overall HTLV-1 prevalence during the course of the study, the prevalence rate decreased from 0.13% (130/100000) in 2009 to 0.07% (70/100000) in 2013. Conclusions The Seroprevalence of HTLV-1 among Iranian blood donors in the regions of our study still is considerable, but there is an obvious declining prevalence over the course of present study. Blood transfusion centers should continually evaluate the residual risk of infection in the country, especially in endemic areas.